The ethics of screening: is 'screeningitis' an incurable disease?. Issue 1 (March 1994) - Shickle, D; Chadwick, R
Abstract : Screening programmes are becoming increasingly popular since prevention is considered 'better than cure'. While earlier diagnosis may result in more effective treatment for some, there will be consequent harm for others due to anxiety, stigma, side-effects etc. A screening test cannot guarantee the detection of all 'abnormal' cases, therefore there will be false reassurance for some. A proper consideration of the potential benefit and harm arising from screening may lead to the conclusion that the programme should not be offered. A modified utilitarian approach may be used for allocation of scarce resources in health care. Ethics has an important role in this evaluation.